INTERNALIZATION OF RELIGION AND CULTURE: RELIGIOSITY OF THE TEBUWUNG SOCIETY IN THE TINGKEPAN TRADITION - Ubaidillah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
This study explains the phenomenon of the living qur'an practiced by the Tebuwung Society in Dukun, Gresik, East Java, regarding the meaning of surah Yusuf and Maryam in the tingkepantradition. The Qur'anic phenomenon in this pregnancy ritual is a form of meaning of the Qur'an's content that surrounds the local community's life. Based on qualitative research with a phenomenological approach, while data were obtained through in-depth interviews, observation, and documentation, this study tries to explain the phenomenon of the tingkepantradition, the public's reception of surahYusuf and Maryam, and the influence of reading the two surahsin the tingkepantradition. Based on Karl Mannheim's perspective and the social construction of Peter L. Berger, the study's results show that the awareness of the Qur'an that exists in the community is built through the religious understanding of the central figures of religion at local level. From these central figures, awareness emerged from understanding the ideas and moral messages of surahYusuf and Maryam in the hope of having descendants that handsome or beautiful face and character as depicted in the two surahs. Apart from being local wisdom, this tingkepan tradition constructively demonstrates the community's belief that the creation of man is closely related to the Oneness of God since he/she was in the womb.